2008
DOI: 10.1002/chem.200800040
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed Intermolecular Hydroarylation of Alkenes with Indoles under Thermal and Microwave‐Assisted Conditions

Abstract: An efficient method for intermolecular hydroarylation of aryl and aliphatic alkenes with indoles using a combination of [(PR(3))AuCl]/AgOTf as catalyst under thermal and microwave-assisted conditions has been developed. The gold(I)-catalyzed reactions of indoles with aryl alkenes were achieved in toluene at 85 degrees C over a reaction time of 1-3 h with 2 mol% of [(PR(3))AuCl]/AgOTf as catalyst. This method works for a variety of styrenes bearing electron-deficient, electron-rich, and sterically bulky substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(20 citation statements)
references
References 129 publications
1
18
0
1
Order By: Relevance
“…Next to the described procedures many related intermolecular FC-type alkylations with styrenes and activated double bonds have been developed using, for instance, InCl 3 /SiO 2 [11], Iodine [62], Ir(III) [51], AuCl 3 /AgSbF 6 [63], AuCl [64], and PtCl 2 [65]. …”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to the described procedures many related intermolecular FC-type alkylations with styrenes and activated double bonds have been developed using, for instance, InCl 3 /SiO 2 [11], Iodine [62], Ir(III) [51], AuCl 3 /AgSbF 6 [63], AuCl [64], and PtCl 2 [65]. …”
Section: Reviewmentioning
confidence: 99%
“…A gold(I)-catalyzed hydroarylation of indoles with styrenes as well as with aliphatic and cyclic alkenes was developed by Che et al [64]. [AuCl(PPh 3 )]/AgOTf was the catalyst system of choice and the reaction was, depending on the substrate, performed under thermal or microwave-assisted conditions.…”
Section: Reviewmentioning
confidence: 99%
“…[3] Another type of hydroarylation reaction of vinylarenes involves the Friedel-Crafts-type alkylation of arenes, wherein a metal catalyst acts as a Lewis acid to activate the double bond of vinylarenes. [4] Although 1,1-diarylethanes are generally obtained from this reaction with good to excellent regioselectivity, the scope of arenes that can participate in this mechanism is severely limited to highly electron-rich arenes, including indoles that contain an electron-donating substitu-ent and a few furan and thiophene derivatives. [4] On the other hand, we recently reported that a nickel/tricyclopentylphosphine (PCyp 3 ) catalyst effects the hydroarylation of 2-vinylnaphthalene with a highly electron-poor arene, pentafluorobenzene.…”
Section: In Memory Of Keith Fagnoumentioning
confidence: 99%
“…These results indicate that all of the hydrogen atoms at the C2 position in 3 aa come from the C2 position of 1 a. [11] Given the result of the above control experiments, two plausible pathways were proposed for this kind of transformation (Scheme 2). In the initial step, regioselective direct electrophilic aromatic palladation at the 3-position of the indole forms an indol-3-ylpalladium species A.…”
Section: Methodsmentioning
confidence: 95%